2021
DOI: 10.3389/fcvm.2021.674612
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Cardiomyopathy: An Emerging Cause of the Embolic Stroke of Undetermined Source

Abstract: Nearly 30% of ischemic strokes have an unknown cause, which are referred to as cryptogenic strokes (CS). Imaging studies suggest that a large proportion of these patients show features that are consistent with embolism, and thus the term embolic stroke of undetermined source (ESUS) was proposed to describe these CS patients. Atrial cardiomyopathy predisposes to thrombus formation and thus embolic stroke even in the absence of atrial fibrillation (AF). This may provide a mechanistic link with ESUS, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
(48 reference statements)
1
19
0
1
Order By: Relevance
“…All of these changes adversely impact ventricular filling, leading to manifestations of HF, and ACM is a frequent cause of HFpEF [ 18 ]. At the same time, atrial alterations lead to an atrial prothrombotic state, even in the absence of atrial arrhythmias, and ACM may be in the causal pathway of cardioembolic stroke independently of AF [ 19 ]. There is no standard diagnosis for ACM, and published studies use heterogeneous methods to define ACM, which are mainly related to electrocardiographic abnormalities of the P wave, the presence of AF, abnormal atrial electrophysiologic (EP) properties on EP studies, abnormal atrial histological features, and increased atrial dimensions or atrial dysfunction on different imaging techniques such as echocardiography or CMR [ 20 ].…”
Section: Definitions and Characterizationmentioning
confidence: 99%
“…All of these changes adversely impact ventricular filling, leading to manifestations of HF, and ACM is a frequent cause of HFpEF [ 18 ]. At the same time, atrial alterations lead to an atrial prothrombotic state, even in the absence of atrial arrhythmias, and ACM may be in the causal pathway of cardioembolic stroke independently of AF [ 19 ]. There is no standard diagnosis for ACM, and published studies use heterogeneous methods to define ACM, which are mainly related to electrocardiographic abnormalities of the P wave, the presence of AF, abnormal atrial electrophysiologic (EP) properties on EP studies, abnormal atrial histological features, and increased atrial dimensions or atrial dysfunction on different imaging techniques such as echocardiography or CMR [ 20 ].…”
Section: Definitions and Characterizationmentioning
confidence: 99%
“…Embolic stroke of undetermined source (ESUS) describes a cryptogenic stroke with embolic pattern on imaging and accounts for ~17% of all ischemic strokes ( 1 ). It is assumed that a relevant part of ESUS is due to an inapparent cardioembolic mechanism including atrial cardiopathy ( 2 , 3 ) and atrial fibrillation (AF) ( 1 ). However, two randomized controlled trials did not show a superiority of oral anticoagulants over antiplatelet therapy in ESUS ( 4 ), implying that a proper work-up for identifying the most probable mechanism of stroke etiology is still warranted in patients who suffered a cryptogenic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…11 These studies suggest that ACM may be the primary cause of LA thrombogenesis and resultant CS. 12 Therefore, identifying the value of ACM may help to better understand the risk of CS in patients without AF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have reported that atrial cardiomyopathy (ACM) was a potential source of embolic stroke of undetermined source (ESUS) in ~45% of ESUS patients 11 . These studies suggest that ACM may be the primary cause of LA thrombogenesis and resultant CS 12 . Therefore, identifying the value of ACM may help to better understand the risk of CS in patients without AF.…”
Section: Introductionmentioning
confidence: 99%